Policy Strengthening Smoking Behavior Screening and Access to Youth Smoking Cessation Services (UBM) in Schools - Setiaji, Bambang; Karyana, Muhammad; Saragih, Benget; Risma, Risma; Putri, Dian Utama Pratiwi (Indonesian Journal of Global Health Research, 2025)
The prevalence of smoking among adolescents aged 10-18 years in Indonesia continues to increase every year from 7.2% in 2013 to 9.1% in 2018. SKI data in 2023 shows that the number of active smokers is estimated to reach 70 million people, with 7.4% of them smokers aged 10-18 years. On the other hand, e-cigarette users among adolescents have increased in the last 4 years, rising from 0,3% in 2019 to 3% in 2021. The 2029 RPJMN mandates that the target prevalence of smokers aged 10-21 years is 6.9%. Meanwhile, Bappenas projects that the prevalence of adolescent smoking in Indonesia in 2030 can reach 16.96% if efforts to prevent and control smoking in adolescents are not carried out optimally. The impact of smoking behavior is not only on individual health, but also public health, potentially triggering chronic diseases, increasing health costs, and threatening the welfare of future generations, especially the Golden Indonesia in 2045. The purpose of this research is as an effort to plan a follow-up to the development of screening and efforts to quit adolescent smoking in schools that are more innovative and attractive to adolescents. This type of research is qualitative research with a case study research design using a policy alternative analysis matrix. There are 17 references used. The stages of the Systematic Literature Review are divided into 4 stages, namely Planning (designing review questions and planning methods), Data Collection (keyword search, title and abstract screening, filtering & assessment, data extraction), Analysis Stage (descriptive and thematic analysis), then ending with Synthesis (discussion). By synthesizing research results through a systematic review approach and presenting them in the form of actionable messages (policy brief and policy paper), more conclusive, comprehensive and balanced facts can be conveyed to stakeholders.